The role of Islamic financing formulas in financing the real estate sector in the United Arab Emirates - Doufi, Guarmia (Finance and Business Economies Review, 2020)
we aim through this research to determine the role of Islamic financing formulas in financing the real estate sector, To determine this role we selected a sample of Islamic banks in the United Arab Emirates Islamic Bank, Dubai Islamic Bank, Abu Dhabi Islamic Bank and Sharjah Islamic Bank, Based on the annual financial reports for the period 2012-2016 to analyze the evolution of mortgage finance in these banks and their contribution to the financing of the real estate sector in the UAE. The results showed that there is an important role for the Islamic financing formulas in financing the real estate sector as a result of the increase in the contribution of the Islamic financing formulas in financing the real estate sector in the UAE, which is estimated at an average percentage10.67 % of 2012-2016, This is a Small but important percentage considering the nombre of institutions and Banks That are active in the sème Field in the UAE.